2011
DOI: 10.3354/ame01459
|View full text |Cite
|
Sign up to set email alerts
|

Active uptake of kleptoplastids by Dinophysis caudata from its ciliate prey Myrionecta rubra

Abstract: We verified an active uptake of kleptoplastids in the toxic and bloom-forming dinoflagellates of the genus Dinophysis from its preferred prey, the ciliate Myrionecta rubra, using a quantitative real-time PCR technique. During a 65 d starvation/feeding experiment with Dinophysis caudata, changes in plastid 16S rRNA, plastid autofluorescence and plastid/nuclear DNA ratio through the cell cycle were followed with quantitative real-time PCR and flow cytometry. During starvation, the cultures initially showed a rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…Similarly, D. caudata fed on M. rubra can also retain these plastids for a long period of time (Park et al 2008), sometimes dispersed in the cytoplasm (Nagai et al 2008) and not within vacuoles (García-Cuetos et al 2010). A recent study verified the active uptake of plastids from M. rubra by D. caudata, which is clear evidence of kleptoplasty, but the possibility of some kind of semi-permanent plastids resident in D. caudata still cannot be excluded (Minnhagen et al 2011). Park & Kim (2010) found bright-orange fluorescent inclusions in the mixotrophic dinoflagellate Fragilidium duplocampanaeforme that had recently ingested Dinophysis caudata and D. acuminata.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, D. caudata fed on M. rubra can also retain these plastids for a long period of time (Park et al 2008), sometimes dispersed in the cytoplasm (Nagai et al 2008) and not within vacuoles (García-Cuetos et al 2010). A recent study verified the active uptake of plastids from M. rubra by D. caudata, which is clear evidence of kleptoplasty, but the possibility of some kind of semi-permanent plastids resident in D. caudata still cannot be excluded (Minnhagen et al 2011). Park & Kim (2010) found bright-orange fluorescent inclusions in the mixotrophic dinoflagellate Fragilidium duplocampanaeforme that had recently ingested Dinophysis caudata and D. acuminata.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of nuclearencoded plastid genes declined as the number of sequestered nuclei disappeared from the population, suggesting that periodic consumption of prey is required by the ciliate to maintain chloroplast function (Johnson et al 2007). Plastid sequestration is commonly observed in ciliates (Stoecker et al 1988) and has recently been confirmed in the dinoflagellate Dinophysis caudata (Minnhagen et al 2011).In contrast, Danish isolates of Mesodinium rubrum maintained the same number of chloroplasts over several divisions in culture, leading to reject the karyoklepty hypothesis in favor of the presence of a permanent endosymbiont. Since it has been clearly demonstrated that they are capable of -and that at least some isolates appear to require -feeding to sustain rapid growth, it has been suggested that M. rubrum depends on periodic ingestion of cryptophyte algae to sustain high growth rates (Johnson 2011).…”
mentioning
confidence: 88%
“…The expression of nuclearencoded plastid genes declined as the number of sequestered nuclei disappeared from the population, suggesting that periodic consumption of prey is required by the ciliate to maintain chloroplast function (Johnson et al 2007). Plastid sequestration is commonly observed in ciliates (Stoecker et al 1988) and has recently been confirmed in the dinoflagellate Dinophysis caudata (Minnhagen et al 2011).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…The processes required for the replication and partitioning of chloroplasts (reviewed by Miyagishima, 2011) have yet to be extensively studied other than in archaeplastids, but appear to rely on the integration of the chloroplast division apparatus with components of the host cytoskeleton. Some components of these pathways are probably not established until late in endosymbiosis, as studies of some relatively stable symbioses suggest that symbiont division ceases after uptake, or that symbionts are only partitioned into one daughter cell following host cell division (Johnson et al, 2006;Minnhagen et al, 2008;Minnhagen et al, 2011;Okamoto and Inouye, 2006). However, the consistent subcellular distributions of many photosynthetic symbionts within host cells -for example the stellate structures formed by multiple kleptoplasts in Dinophysis, or the sublamellar distribution of kleptoplasts in Myrionecta (Garcia-Cuetos et al, 2010) -suggest that partitioning of symbionts by the host cytoskeleton might commence early in the process of chloroplast establishment.…”
Section: How To Avoid Immediate Destruction?mentioning
confidence: 99%